PEMBERDAYAAN MASYARAKAT DALAM PENGGUNAAN TANAMAN SELEDRI SEBAGAI ANTIHIPERTENS DI MARGALUYU KELURAHAN MARGASARI, KECAMATAN BUAH BATU, BANDUNG.: PEMBERDAYAAN MASYARAKAT DALAM PENGGUNAAN TANAMAN SELEDRI SEBAGAI ANTIHIPERTENS DI MARGALUYU KELURAHAN MARGASARI, KECAMATAN BUAH BATU, BANDUNG. - Lilis Febriyanti; Yayat Sudaryat; Irvan Herdiana (Poltekkes Kemenkes Bandung, 2022)
n the world, hypertension is ranked third as a risk factor for death. In 2025, the increase in cases of hypertension, especially in developing countries, is estimated to be around 80% of the 639 million cases in 2000 or around 1.15 billion cases (Pusparini, 2015). In botany, celery leaves are said to contain Apigenin which can prevent constriction of blood vessels and Phthalides which can relax artery muscles or relax blood vessels. These substances regulate blood flow, allowing blood vessels to dilate and reduce blood pressure. Based on this, it is necessary to empower the community in the use of celery plants to overcome hypertension problems, which is carried out in the Community Service program in the PKM scheme with partners being PKK Cadres RW 09 in Margasari Village, Buah Batu District, Bandung. This PKM activity took place in seven activities, namely: Checking participants' blood pressure before being treated with celery plants, conducting pre-tests on participants before counseling was carried out, weighing celery plants to be distributed to each participant so they could be self-medicating at home, conducting lectures and discussions about hypertension, antihypertensive chemical drugs, and the use of antihypertensive celery plants, demonstrations of making herbal celery drinks which are efficacious as antihypertensives and distributing drinks to participants, carrying out post tests, and checking participants' blood pressure after being treated with celery plants for 3 days . The solution offered is an increase in the knowledge, attitudes, and skills of the PKM partners as indicated by an increase in the post-test scores when compared to the pre-test scores. In addition, there was also an increase in the degree of public health with a decrease in blood pressure, especially in participants who suffered from hypertension after being treated with celery leaves.